Performance of the existing classification criteria for gout in Thai patients presenting with acute arthritis - Kanon Jatuworapruk (2018)
© 2016 Wolters Kluwer Health, Inc. Currently, there are 5 existing classification criteria for gout: the Rome, New York, American Rheumatism Association (ARA), Mexico, and Netherlands criteria. This study was carried out to determine the performance of these classification criteria in Thai patients presenting with acute arthritis. All consecutive patients presenting with acute arthritis and being consulted at the Rheumatology Unit, Chiang Mai University Hospital from January 2013 to May 2015 were invited to join the study. Gout was defined by the presence of monosodium urate crystals in the synovial fluid or tissue examined by experienced rheumatologists. The 5 existing gout classification criteria were performed and evaluated in all of the patients, who were divided in subgroups of early disease (2 years), established disease (>2 years), and those without tophus. There were 136 gout and 97 nongout patients. Sensitivity and specificity across all criteria ranged from 75.7% to 97.1% and 68.0% to 84.5%, respectively. Overall, the Mexico criteria had the highest sensitivity (97.1%), and the ARA survey criteria the highest specificity (84.5%), whereas the Mexico criteria performed well in early disease with sensitivity and specificity of 97.1% and 81.7%, respectively. All 5 criteria showed high sensitivity (from 76.4% to 99.1%) but low specificity (from 30.8% to 65.4%) in established disease. In patients without tophus, the sensitivity and specificity ranged from 64.1% to 95.7% and 68.8% to 85.4%, respectively. The ARA survey criteria across all groups showed consistently high specificity for gout. The 5 existing classification criteria for gout had limited sensitivity and specificity in Thai patients presenting with acute arthritis. The ARA survey criteria are the most suitable for diagnosing gout in Thai people when crystal identification is not available.